Failure of High Dosage Valium in the Treatment of Neonatal Tetanus - Tjandra Husada; Muzief Munir (Paediatrica Indonesiana, 1980)
The fact that the mortality rate of neonatal tetanus is still high, and that the use of high dosage of valium has been reported to be of no side effect, encouraged the authors to use a high dosage of valium in the treatment of neonatal tetanus particularly in severe cases. This study was performed on 35 cases using 20-30 mg/kg bw/day of valium from July 1, 1976 through October 1977. The outcome of this study indicates that the treatment of neonatal tetanus using high dosage valium remained poor, where 22 out of 35 cases died (62.9%) with the following specifications: all of 6 mild cases survived, 2 out of 6 of moderate cases died, 20 out of 23 severe cases died. The authors believe that the simplest and the more effective way to overcome this disease is to give either tetanus prophylaxis to expectant mothers or 1500 U ATS prophylaxis to every newborn delivered by a traditional midwife (dukun bersalin).